Oral health patterns of independently living dentate older people: a cross‐sectional survey of dental attendees in south‐east London. (24th January 2013) - Al‐Haboubi, Mustafa; Zoitopoulos, Liana; Beighton, David; Gallagher, Jennifer
<x xml:space="preserve">Abstract</x> Background The oral health needs of older adults present increasing challenges to dental services. Objectives To examine the clinical oral health status of dentate older people living in the community and attending dental services. Methods One hundred and eighty‐six dentate adults, aged ≥60 years, underwent clinical examination (DMFS, Plaque and Gingival Indexes), salivary analysis and completed a questionnaire. Results Participants had an average of 21.4 (±6.2) teeth present and 1.2 (±3.0) decayed, 51.0 (±28.8) missing and 32.6 (±20.5) restored surfaces. Individuals living in the most deprived areas had significantly lower numbers of teeth than those in the least deprived areas (19.1 ± 7.5 cf 23.8 ± 4.1; p < 0.001). Whilst there were no significant differences in DMFS score, residents in the most deprived areas had significantly more missing and fewer filled surfaces than those in the least deprived areas (p = 0.001 and p < 0.001, respectively). Participants with ≥21 teeth (64%) had lower plaque scores, fewer decayed root surfaces, higher stimulated saliva flow rates and lower salivary lactobacilli and yeast counts than those with <21 teeth (p < 0.05 for all). Conclusions The findings highlight differences in clinical oral health by age and deprivation status and underline the importance of saliva and retaining a functional dentition.